An equilibrium model of credit rating agencies - Steinar Holden; Gisle James Natvik; Adrien Vigier (University of Oslo, Department of Economics, 2013)
We develop a model of credit rating agencies (CRAs) based on reputation concerns. Ratings a ffect investors' choice and, thereby, also issuers' access to funding and default risk. We show that in equilibrium - the informational content of credit ratings is inferior to that of CRAs' private information. We fi nd that CRAs have a pro-cyclical impact on default risk: in a liquidity boom CRAs help resolve investors' coordination problem, and lower the probability of default; in a liquidity crunch CRAs raise the probability of default. Furthermore, rating standards tend to be pro-cyclical, while biased CRA-incentives will ultimately be self-defeating.
Keywords: G24; G33; D82; C72; 330; credit rating agencies; global games; coordination failure; Ratingagentur; Kreditwürdigkeit; Gleichgewicht; Nichtkooperatives Spiel; Asymmetrische Information